Investigation of Epstein-Barr virus DNA in formalin-fixed and paraffin-embedded breast cancer tissues - Kalkan, A; Ozdarendeli, A; Bulut, Y; Yekeler, H; Cobanoglu, B; Doymaz, MZ (Karger, 2005)
Objective: To investigate etiological role of Epstein-Barr virus (EBV) DNA in breast cancer. Materials and Methods: The presence of EBV DNA in 57 breast cancer tissues was investigated with a sensitive PCR assay. The breast cancer tissues were from invasive ductular (n = 28), lobular (n = 20) and other miscellaneous carcinomas (n = 9). Tissues from normal breasts and patients with various benign breast diseases (n = 55): fibrocystic disease (n = 34), fibroadenoma (n = 16), hyperplasia, and granulomatous mastitis (n = 5), were used as control samples. Results: EBV DNA was detected in 13 (23%) cancerous tissues (7 ductular, 4 lobular, 2 other carcinoma) and 19 (35%) in the control tissues. The difference between EBV presence in malignant and benign tissues was not statistically significant (p > 0.05). Conclusion: The presence of EBV DNA was detected almost equally in both breast cancer and normal tissues, which indicates no etiological role for EBV in breast cancer. We suggest further etiological studies. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: Epstein-Barr virus; breast cancer; polymerase chain reaction